PEMBINAAN PTK-PNF SEBAGAI UPAYA PENINGKATAN KUALITAS SDM - Puspita, Widya Ayu (JIV-Jurnal Ilmiah Visi, 2007)
Teachers and education personnel of nonformal education play an important and significant role in educating Indonesian people all of the country. They function as the front layers in implementing all programs of nonformal education. The quality of nonformal education, therefore, is determined by the quality and the quantity of teachers and education personnel of nonformal education. For this reason their competence or ability should be developed through a well planned program continuously and systematically. This article discusses three strategic agenda to develop the quality of teachers and education personnel of nonformal education. They are the establishment of professional association for teachers and education personnel of nonformal education, certification of teachers and education personnel of nonformal education, and development of the draft of legal rules for the status, roles functions and responsibilities of teachers and education personnel of nonformal education.